2021
DOI: 10.1038/s41586-021-03477-4
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutation landscapes at single-molecule resolution

Abstract: Somatic mutations drive cancer development and may contribute to ageing and other diseases. Yet, the di culty of detecting mutations present only in single cells or small clones has limited our knowledge of somatic mutagenesis to a minority of tissues. To overcome these limitations, we introduce nanorate sequencing (NanoSeq), a new duplex sequencing protocol with error rates <5 errors per billion base pairs in single DNA molecules from cell populations. The version of the protocol described here uses clean gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
382
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(413 citation statements)
references
References 58 publications
30
382
1
Order By: Relevance
“…While multiple S protein mutations, i.e. B.1.1.7 variant, have been associated with the severity of COVID-19 [ 17 , 18 ], this is not the case for our patients. Our samples did not consist of B.1.1.7 variant.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…While multiple S protein mutations, i.e. B.1.1.7 variant, have been associated with the severity of COVID-19 [ 17 , 18 ], this is not the case for our patients. Our samples did not consist of B.1.1.7 variant.…”
Section: Discussioncontrasting
confidence: 55%
“…These variants might be associated with some potential advantages for these viruses. While the B.1.1.7 variant has been associated with COVID-19 clinical severity [ 17 , 18 ], the 501.V2 and P.1 variants have not [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future strategies may involve digesting single-stranded DNA irrespective of whether it contains a recognizable lesion, or labelling resynthesized bases and excluding from analysis. Noteworthily, Abascal et al recently reported nanorate sequencing (NanoSeq) that suppresses strand resynthesis during ER/AT by using a restriction enzyme to digest intact DNA to produce blunted dsDNA fragments and then non-A dideoxynucleotides during dA-tailing to block templated extension 31 . As a result, NanoSeq can achieve a reported error rate of < 5e-9 when applied to gDNA extracted from sperm and cord blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…Unique molecular identifiers (UMIs) have been developed to suppress the errors to detect mutations below 0.1% VAF 19,20 . Recent advances in DuplexSeq 21 , NanoSeq 22 and SaferSeqS 23 has further reduced errors by grouping both strands of a DNA molecule together into a duplex family to distinguish DNA damage with real mutation achieving confident variant calling at 0.01% VAF or lower. However, since all template molecules, regardless of wild type or variant molecules, are sequenced redundantly in current UMI-based methods, they require sequencing to extremely high depths proportional to input molecule amount.…”
Section: Introductionmentioning
confidence: 99%
“…We introduced different UMI sequences to each strand of DNA molecule by PCR and thus duplex family information is lost during denaturation of UMI attachment PCR. We expect that error from DNA damage may be further suppressed in QBDA by using ligation-based UMI attachment, so that in downstream bioinformatics analysis both strands of a DNA molecule can be grouped into a duplex family similar to DuplexSeq 21 , NanoSeq22 and SaferSeqS23 while still reducing sequencing depth by BDA variant enrichment. The gene ploidy impacts VAF in QBDA, but QBDA is able to accurately quantitate VAF in case CNV and mutation are simultaneously present in the gene of interest as long as copy number for the gene is normalized.…”
mentioning
confidence: 99%